LEGAL RELATIONS IN THE USAGE OF LETTER OF VALUE AND BANKING INSTRUMENTS AS A MEANS OF PAYMENT - Chamdani; Indradjaja, Nobella; Sonny Wijaya (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
In order to facilitate transactions, the banking sector determines several forms of payments, such as in real money, paper based and e-money. As a form of payment and receivable account, paper money holds function equivalent to real money, which are authenticated in negotiable instruments. The usage of negotiable instruments and the cashing are regulated in several agreements between the two parties, which are also involve another party like Bank Indonesia or the affiliates. This research is conducted with the intention of observing the forms and systems of payment using Securities and Banking Notes, as well as how the legal relationship between the issuer of securities and the holder of securities. Normative legal research methods is used to find the basis, principles and doctrines of law as an effort to overcome the legal issues that are the focus of research. Although, in such a contract, the legal basis of law is needed since negotiable instruments are often used as a payable form in several transactions which affects in ownership changes. Thus, for these cases, there are four theories that can be used: Creatief Theories, Vertoning Theories, Overeenkomst Theories, and Redelijkhesdist Theories. The issuance of SBPU is done to regulate the rate of demand deposits that replace the function of money, SB also holds a function as a letter that guarantees the receivables and obligations of the party who has a debt.